2020
DOI: 10.1093/mnras/staa3184
|View full text |Cite
|
Sign up to set email alerts
|

NLTT5306B: an inflated, weakly irradiated brown dwarf

Abstract: We present Spitzer observations at 3.6 and 4.5 microns and a near-infrared IRTF SpeX spectrum of the irradiated brown dwarf NLTT5306B. We determine that the brown dwarf has a spectral type of L5 and is likely inflated, despite the low effective temperature of the white dwarf primary star. We calculate brightness temperatures in the Spitzer wavebands for both the model radius, and Roche Lobe radius of the brown dwarf, and conclude that there is very little day-night side temperature difference. We discuss vario… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 45 publications
4
32
0
Order By: Relevance
“…Based on the given mass ratio (0.1), orbital separation (0.003au), and brown dwarf radius (0.7 R Jup ), the modeled distortion for SDSS1411-B is around 0.67%. The model calculation is the same as that in Casewell et al (2020a). The fitted orbital period of 2.02863 ± 0.00008 hours, or 121.718 ± 0.005 minutes is within 2-σ of the reported period of 121.73 minutes in Beuermann et al (2013).…”
Section: Day-night Contrast and Mid-eclipse Timementioning
confidence: 66%
“…Based on the given mass ratio (0.1), orbital separation (0.003au), and brown dwarf radius (0.7 R Jup ), the modeled distortion for SDSS1411-B is around 0.67%. The model calculation is the same as that in Casewell et al (2020a). The fitted orbital period of 2.02863 ± 0.00008 hours, or 121.718 ± 0.005 minutes is within 2-σ of the reported period of 121.73 minutes in Beuermann et al (2013).…”
Section: Day-night Contrast and Mid-eclipse Timementioning
confidence: 66%
“…However given the long period of the system, and the high mass of the brown dwarf, we determine it to be unlikely that these effects would transfer enough heat into the brown dwarf to inflate it. Casewell et al (2020) consider the white-dwarf brown-dwarf binary NLTT5036, which also shows signs of inflation. They show that regardless of the level or irradiation experienced, low mass brown-dwarfs (M<35M Jup ) are able to be inflated when heated by their host star.…”
Section: Inflated Brown Dwarf Radiimentioning
confidence: 99%
“…However with so few transiting brown dwarfs yet discovered, whether this relationship continues into the substellar regime is unclear. It has been suggested that brown dwarfs may be able to be inflated if they orbit host stars that are particularly active (Casewell et al 2020). A comparison with evolutionary models would suggest that high mass brown dwarfs are much less likely to be inflated, regardless of the effect of their host star.…”
Section: Introductionmentioning
confidence: 99%
“…While NLTT 5306 B does not fill its Roche lobe, near-IR spectra from SpeX on the NASAInfraRed Telescope Facility have shown evidence of intermediate gravity, with ( ) g log 4.8, suggesting the brown dwarf is inflated (Casewell et al 2020a). In exoplanets, significant levels of UV irradiation onto a planet from its host can cause the planetary atmosphere to inflate and evaporate (e.g., Demory & Seager 2011).…”
Section: Introductionmentioning
confidence: 99%